Bipteria vetusta n. sp. – an old parasite in an old host: tracing the origin of myxosporean parasitism in vertebrates - Kodádková, Alena; Bartošová-Sojková, Pavla; Holzer, Astrid S; Fiala, Ivan (International journal for parasitology, 2015)
Myxosporea (Myxozoa), a group of parasitic Cnidaria, use mostly bony fishes (Teleostei) as intermediate hosts; however, they can also parasitize other vertebrates such as cartilaginous fish (Chondrichthyes). Molecular data of myxosporeans from sharks and rays (Elasmobranchii) revealed these parasites to be one of the most basal representatives in the myxosporean phylogenetic tree, suggesting their ancient evolutionary history. A new myxosporean species, Bipteria vetusta n. sp., was found in the gall bladder of rabbit fish, Chimaera monstrosa (Holocephali; Chondrichthyes), and ssrDNA-based phylogeny revealed its basal position within the marine myxosporean lineage. Molecular dating based on ssrDNA analysis suggested the origin of a stem lineage leading to the marine myxosporean lineage at the time of the origin of Chondrichthyes in the Silurian era. The two common lineages of Myxozoa, Myxosporea and Malacosporea, were estimated to have split from their common ancestor in the Cambrian era. Tracing the history of evolution of the "vertebrate host type" character in the context of molecular dating showed that cartilaginous fish represented an ancestral state for all myxosporeans. Teleosts were very likely subsequently parasitized by myxozoans four times, independently. Myxosporean radiation and diversification appear to correlate with intermediate host evolution. The first intermediate hosts of myxosporeans were cartilaginous fish. When bony fish evolved and radiated, myxosporeans switched and adapted to bony fish, and subsequently greatly diversified in this new host niche. We believe that the present study is the first attempt at molecular dating of myxozoan evolution based on an old myxosporean species – a living myxosporean fossil.
Keywords: RNA ribozomální 18S; biologická evoluce; Co-evolution; interakce hostitele a parazita; Holocephali; Vertebrate host; Animals; molekulární sekvence - údaje; ribozomální DNA; Biological Evolution; shluková analýza; Myxosporean evolution; Cluster Analysis; Cartilaginous fish; Molecular clock; Molecular Sequence Data; Myxozoa; RNA, Ribosomal, 18S; Sequence Analysis, DNA; Gallbladder; Host-Parasite Interactions; Fishes; zvířata; fylogeneze; sekvenční analýza DNA; DNA, Ribosomal; ryby; Phylogeny; žlučník; Bipteria